2018
DOI: 10.1163/15685411-00003170
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcoding, phylogeny and phylogeography of the cyst nematode species of the Avenae group from the genus Heterodera (Tylenchida: Heteroderidae)

Abstract: SummaryAmong the recognised species groups ofHeterodera, theAvenaegroup is one of the largest with a total of 12 species. Ten of them,H. arenaria,H. aucklandica,H. australis,H. avenae,H. filipjevi,H. mani,H. pratensis,H. riparia,H. sturhaniandH. ustinovi, are morphologically closely related and represent theH. avenaespecies complex, and the other two,H. hordecalisandH. latipons, are morphologically more distinct from this complex. In this study we provide comprehensive phylogenetic analyses of several hundredC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 70 publications
(97 reference statements)
0
14
0
Order By: Relevance
“…Using morphological and molecular characteristics, the species of this genus have been divided into nine groups, i.e., Afenestrata, Avenae, Bifenestra, Cardiolata, Cyperi, Goettingiana, Humuli, Sacchari, and Schachtii. Morphological characterization of Heterodera species is mainly done based on vulva-slit length, vulval cone fenestration, presence or absence of bullae and underbridge in female cysts, and stylet length, lateral field differentiation, tail length, and hyaline tail length in J2 (Subbotin et al, 2010). Since the last two decades, employing molecular data such as ITS and 28S of ribosomal DNA and COI gene of mitochondrial DNA to characterize Heterodera species has been a common practice, including DNA barcoding, phylogeny, and even phylogeography (Ferris et al, 1999;Toumi et al, 2013a;Subbotin et al, 2017Subbotin et al, , 2018.…”
mentioning
confidence: 99%
“…Using morphological and molecular characteristics, the species of this genus have been divided into nine groups, i.e., Afenestrata, Avenae, Bifenestra, Cardiolata, Cyperi, Goettingiana, Humuli, Sacchari, and Schachtii. Morphological characterization of Heterodera species is mainly done based on vulva-slit length, vulval cone fenestration, presence or absence of bullae and underbridge in female cysts, and stylet length, lateral field differentiation, tail length, and hyaline tail length in J2 (Subbotin et al, 2010). Since the last two decades, employing molecular data such as ITS and 28S of ribosomal DNA and COI gene of mitochondrial DNA to characterize Heterodera species has been a common practice, including DNA barcoding, phylogeny, and even phylogeography (Ferris et al, 1999;Toumi et al, 2013a;Subbotin et al, 2017Subbotin et al, , 2018.…”
mentioning
confidence: 99%
“…For this reason, a qPCR assay based on the differences of another gene sequence was developed to discriminate between the Heterodera avenae group species ( H. avenae , H. filipjevi , and H. latipons ) by targeting the CO I gene (Toumi et al, 2013, 2015). Several studies have adopted the CO I gene for the DNA barcoding of the Heteroderidae family (Powers et al, 2018; Subbotin et al, 2018; Vovlas et al, 2015). According to Subbotin et al (2018), the CO I gene is a powerful barcoding marker because each species of Heterodera has a unique sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have adopted the CO I gene for the DNA barcoding of the Heteroderidae family (Powers et al, 2018; Subbotin et al, 2018; Vovlas et al, 2015). According to Subbotin et al (2018), the CO I gene is a powerful barcoding marker because each species of Heterodera has a unique sequence. Furthermore, the Consortium for the Barcode of Life proposed to barcode all known species according to the DNA sequence of the CO I gene (Blok and Powers, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the wide distribution of EHA population, CHA was only found in China. Subbotin et al ( 2018 ) showed that CHA has low mtCOI genetic diversity based on limited samples. This suggests that CHA may have gone through a strong bottleneck as a result of being associated with a domesticated host, and thus their dissemination may associate with its host.…”
Section: Introductionmentioning
confidence: 99%